Mutual fund flows, expected returns, and the real economy - Stephan Jank (University of Cologne, Centre for Financial Research (CFR), 2011)
The paper explores whether the co-movement of market returns and equity fund flows can be explained by a common response to macroeconomic news. I find that variables that predict the real economy as well as the equity premium are related to mutual fund flows. Changes in dividend-price ratio explain mutual fund flows beyond the information contained in returns. Further predictive variables such as default spread, relative T-Bill rate and, in particular consumption-wealth ratio also explain mutual fund flows. Mutual fund flows are, in accordance with the information-response hypothesis, forward-looking and predict real economic activity.
Keywords: G12; G14; 330; aggregate mutual fund flows; equity premium; return predictability; asset pricing